Eighteen capitals of China - Geil, William Edgar (J. B. Lippincott company, 1911)
The southern capitals: Hangchow. Foochow. Canton. Kweilin. Kweiyang. Yunnanfu.--The Yangtze capitals: Soochow. Nanking. Anking. Nanchang. Wuchang. Changsha. Chengtu.--The Yellow capitals: Lanchow. Sian. Kaifeng. Taiyuanfu. Tsinan. Peking: capital of capitals.